On energy of prime ideal graph of a commutative ring associated with transmission-based matrices - Romdhini, Mamika Ujianita; Nawawi, Athirah; Husain, Sharifah Kartini Said; Al-Sharqi, Faisal; Purnamasari, N.A. (Universiti Putra Malaysia, 2024)
This research explores the energy of the prime ideal graph of a commutative ring. The study demonstrates the energy formula of the graph associated with transmission-based matrices. Through research, the findings highlight the distance, Wiener-Hosoya, and distance signless Laplacian matrices. It should be noted that the distance and Wiener-Hosoya energies are always twice their spectral radius, meanwhile, it does not hold for distance signless Laplacian energy.